A new approach to vocal cord leukoplakia and evaluation of proton pump ınhibitor treatment. - Ozturan, ORHAN; Sezen, Goktas; DOĞAN, REMZI; ÇALıM, ÖMER FARUK; YENİGÜN, ALPER; YENIGUN, A; ÇALIM, ÖMER FARUK; DOGAN, REMZİ; ÖZTURAN, ORHAN; TUGRUL, SELHATTİN; TUĞRUL, SELAHATTİN (My University, 2019)
Purpose: Our aim is identify a new approach to vocal cord leukoplakia treatment and detect to efficiency of proton pump inhibitors. Study design: Prospective, nonrandomized experimental clinical trial. Methods: A 'First Assessment Scale' was prepared. This scale included the lesion's and the patient's characteristics. Using this scale, 24 patients included to the study. 20 mg rabeprazole twice daily was applied to all patients. At the end of 3rd month, a 'Second Assessment Scale' was used and two groups created. In group 1, 19 patients were accepted to responsive for the therapy and received the same therapy. The group 2 was included five patients that accepted unresponsive to treatment and directed to surgery. All patients received the same treatment additionally 3 months. At the end of 6th month, the Reflux Symptom Index (RSI), the Reflux Finding Score (RFS) and the Red-Green-Blue (RGB) values evaluated and comparisons were made. Results: The RSI and RFS values were significantly decreased in all patients. The Red values were significantly decreased with treatment in group 1, but the Green and Blue values were not. In group 2, the RGB values were not showed the significant differences. In conclusion, seven patients (29,2%) showed complete lesion regression, 12 patients (50%) showed partial lesion regression and five patients (20,8%) showed no response to treatment. Conclusions: The proton pump inhibitor treatment may be beneficial for the selected patients. The scales that we prepared were useful for lesion assesment.